2020
DOI: 10.1590/0034-7167-2020-0032
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of tissular integrity in patients with diabetic foot

Abstract: Objective: Evaluate the impairment of tissue integrity in patients with diabetic foot and verify its association with time of diagnosis of the disease. Methods: Cross-sectional study conducted with 134 patients in an outpatient clinic located in the Northeast region of Brazil. A semi-structured questionnaire was used for data collection, which was subjected to descriptive analysis and the Mann-Whitney U non-parametric test. Results: Indicators with the lowest average score were: skin temperature, sweating, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
0
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
1
0
0
3
Order By: Relevance
“…The sociodemographic characteristics of the sample were similar to those described by other studies. The frequency of the age variable agrees with recent studies that found relevant prevalence rates of type 2 diabetes in people aged 60–79 (Assunção et al., 2017; Gontijo et al., 2020). Type 2 diabetes mellitus stands out directly in the scope of chronic diseases of high incidence and prevalence in the world scenario mainly due to the transformation in demographic profile as the population ages.…”
Section: Discussionsupporting
confidence: 90%
“…The sociodemographic characteristics of the sample were similar to those described by other studies. The frequency of the age variable agrees with recent studies that found relevant prevalence rates of type 2 diabetes in people aged 60–79 (Assunção et al., 2017; Gontijo et al., 2020). Type 2 diabetes mellitus stands out directly in the scope of chronic diseases of high incidence and prevalence in the world scenario mainly due to the transformation in demographic profile as the population ages.…”
Section: Discussionsupporting
confidence: 90%
“…Esse fato condiz com a diminuição do autocuidado entre os pacientes com maior tempo de diagnóstico. Desse modo, os profissionais de saúde da atenção primária devem fortalecer a prática do cuidado com os pés e buscar traçar maiores intervenções de assistência ao longo do tratamento para identificar precocemente estas condições 9,10 .…”
Section: Discussionunclassified
“…O aumento da prevalência das DCNT tem se destacado, mundialmente, devido às suas elevadas taxas de morbidade e mortalidade. Esse crescimento está associado a maior expectativa de vida da população e à modificação no consumo alimentar e no estilo de vida (GONTIJO et al, 2020). Dentre as DCNT, destaca-se a Diabetes Mellitus (DM), um problema de saúde pública relevante no Brasil e no mundo devido à magnitude do número de indivíduos afetados pela DM tipo 2 (DM2), correspondendo de 90 a 95% dos que sofrem dessa doença (OGGIAM; KUSAHARA; GAMBA, 2021).…”
Section: Introductionunclassified